Quality of Life in Schoolchildren, Their Parents and Teachers during the COVID-19 Pandemic: Psychosomatic Health, Teachers’ and Parents’ Burnout Along with the Prevalence of Depressive and Anxiety Symptoms - Mudło-Głagolska, Karolina; Larionow, Paweł (Przegląd Badań Edukacyjnych (Educational Studies Review), 2022)
The COVID-19 pandemic and the related changes in the implementation of educational activities affected three groups of the school community: schoolchildren, their parents and teachers. The purpose of this study is to assess psychological functioning in these groups in the period before returning to full-time face-to-face education. The study involved 88 schoolchildren, 99 parents and 36 teachers from Poland. Life satisfaction, subjective physical and mental health complaints as well as the quality of life were assessed in students. Anxiety and depressive symptoms, teachers’ and parental burnout were also studied. Additionally, the usage of such maladaptive coping strategies as rumination was assessed in teachers. The analysis revealed that lower levels of psychological well-being were shown by girls (compared to boys) and schoolchildren from grades 7 to 8 (compared to younger pupils). Teachers scored relatively high on the anxiety/depressive symptoms and work burnout scales. In contrast, parents had lower levels of anxiety/depressive symptoms and the level of parental burnout was average. Among the participants of the educational process, pupils in the higher grades (7–8), especially girls, as well as teachers had poorer well-being. We suggest that measures should be taken to provide psychological support to these risk groups.